The Effect of Audit Tenure, Audit Rotation and Client's Company Size on Audit Quality with Audit Fee as Moderating Variable - Humaira Dinda Mulyadi; Dhini Suryandari (Profesional Muda Cendekia Publishing, 2021)
Transparency of financial reports is one of the important things for decision-makers. In proving that financial statement information has been presented fairly, companies need independent parties, one of which is the audit services provided by the Public Accounting Firm (PAF). Good or bad Audit Quality for the information presented really depends on the auditor in carrying out his duties. This research was conducted at Financial Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2015 - 2019. This research was conducted using quantitative methods and sample selection using purposive sampling method. The analysis used in this research is binary logistic regression. The results showed that Audit Tenure and Audit Rotation had no effect on Audit Quality, Client's Company Size had a negative effect on Audit Quality, and Audit Fees had a positive effect on Audit Quality. Audit Fee Interactions are unable to moderate the effect of Audit Tenure and Audit Rotation on Audit Quality, while Audit Fee Interactions are able to weaken the influence of Client's Company Size on Audit Quality. Suggestions from this research are expected to all companies that have high complexity to choose a PAF that suits the audit needs and not too pressurize the Audit Fee given. In addition, companies need to pay attention to Audit Tenure again by considering from a cost-benefit analysis point of view. For future researchers, it is expected to extend the research period and use Audit Quality proxies, population, methods, and analysis tools outside of this study.